2015
DOI: 10.1016/j.amepre.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mental Health Benefits Legislation

Abstract: Context Health insurance benefits for mental health services typically have paid less than benefits for physical health services, resulting in potential underutilization or financial burden for people with mental health conditions. Mental health benefits legislation was introduced to improve financial protection (i.e., decrease financial burden) and to increase access to, and use of, mental health services. This systematic review was conducted to determine the effectiveness of mental health benefits legislatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 56 publications
3
29
0
Order By: Relevance
“…Further, our methods limited our ability to probe for the mechanisms by which policy levers influenced access and utilization outcomes. For example, state or federal mental health benefits legislation could reduce mental health coverage restrictions, in turn leading to reduced family out-of-pocket costs paid for services and subsequent increase in service utilization (Sipe et al 2015). Although this is a common shortcoming in existing literature (Moulton et al 2009; Shonkoff 2017), future studies could disentangle these mechanisms to facilitate causal inferences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, our methods limited our ability to probe for the mechanisms by which policy levers influenced access and utilization outcomes. For example, state or federal mental health benefits legislation could reduce mental health coverage restrictions, in turn leading to reduced family out-of-pocket costs paid for services and subsequent increase in service utilization (Sipe et al 2015). Although this is a common shortcoming in existing literature (Moulton et al 2009; Shonkoff 2017), future studies could disentangle these mechanisms to facilitate causal inferences.…”
Section: Discussionmentioning
confidence: 99%
“…For PubMed, Medical Subject Headings (MeSH) terms were also included. Search terms were tailored to each database, informed by the literature (Miles et al 2010; Sipe et al 2015; Spencer and Komro 2017) and based on four dimensions of interest: (a) problem or condition (e.g., anxiety, conduct disorder); (b) treatment (e.g., group therapy); (c) categories or intended outcomes of policy levers of interest (e.g., availability); and (d) treatment target (e.g., caregiver, teacher) (Table 1). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Task Force finding is based on evidence from a systematic review 6 of 30 studies reported in 37 papers (search period, 1965-March 2011). Of these, 28 studies examined the effects of state or federal mental health parity legislation or policies, and two studies examined the effects of state-mandated coverage for mental health and substance abuse care; these studies generally found favorable effects.…”
Section: Basis Of Findingmentioning
confidence: 99%
“…The systematic review 6 identified several evidence gaps that need to be addressed in future studies of mental health benefits legislation. There is limited research investigating the effects of mental health benefits legislation on mental health outcomes.…”
Section: Effectiveness Evidence Gapsmentioning
confidence: 99%